Characteristics and outcomes of patients treated with apremilast in the real world: results from the APPRECIATE study. (30th July 2020) - Augustin, M.; Kleyn, C.E.; Conrad, C.; Sator, P.G.; Ståhle, M.; Eyerich, K.; Radtke, M.A.; Bundy, C.; Mellars, L.; Greggio, C.; Cordey, M.; Koscielny, V.; et al.
Abstract: Background: APPRECIATE is a multinational, observational, retrospective, cross‐sectional study in patients treated for psoriasis with apremilast, an oral phosphodiesterase 4 inhibitor. Objectives: To describe the characteristics of patients with psoriasis treated with apremilast in the clinical setting, to evaluate real‐world outcomes of psoriasis treatment with apremilast and to better understand the perspectives of patients and physicians on treatment outcomes. Methods: In six European countries, patients with chronic plaque psoriasis treated in clinical practice who could be contacted 6 (±1) months after apremilast initiation were enrolled. Patient characteristics, Dermatology Life Quality Index (DLQI) and Psoriasis Area and Severity Index (PASI) were obtained from medical records when available. Outcomes were evaluated using patient/physician questionnaires. Results: In 480 patients at treatment initiation, mean [median; 95% confidence interval (CI)] PASI and DLQI scores were 12.5 (10.7; 11.6–13.4) and 13.4 (13.0; 11.4–14.2), respectively. At 6 (±1) months, 72.3% of patients ( n = 347) continued apremilast treatment [discontinuations: lack of efficacy (13.5%), safety (11.7%), other (2.5%)]. In patients continuing treatment, 48.6% achieved a ≥75% reduction in PASI score; mean (95% CI) DLQI score was 5.7 (4.5–6.9), and mean (SD) Patient Benefit Index score was 2.8 (1.2). Physicians perceived clinical improvement in 75.6% of patients. Physicians' perspective on overall success of apremilast in meeting expectations correlated with patients' perception of treatment benefit ( r = 0.691). Most commonly reported adverse events (>5% of patients) were diarrhoea, nausea and headache. Conclusions: Patients in APPRECIATE reported high disease burden despite more moderate skin involvement than those who enrolled in clinical trials of apremilast. Findings from APPRECIATE demonstrate the real‐world value of apremilast for psoriasis treatment, as 7 of 10 patients continued therapy and showed notable improvement in disease severity and quality of life 6 (±1) months after apremilast initiation. Abstract : Linked Commentary: P. Gisondi et al. J Eur Acad Dermatol Venereol 2021; 35: 13. https://doi.org/10.1111/jdv.17067 .